Implementasi Algoritme Salsa20 untuk Pengamanan Search Keyword Dokumen Terenkripsi - Muhammad Thareq Parsaulian Beyri; Ari Kusyanti; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
As the digital era develops, large-sized storage media are needed by many groups such as companies, government agencies, and organizations to store data or files. Also, storage media are needed that can facilitate more than one user in accessing data anywhere simultaneously. Cloud storage answers these needs. The stored data will be placed on the server. However, with the convenience provided by cloud storage, some aspects need to be considered by the user, namely the security of user data so that the data can only be accessed by the data owner or the party is given access. By applying encryption, data can only be accessed by the owner of the encryption key. In this study the encryption algorithm used is Salsa20. Salsa20 algorithm is a proven algorithm for its level of security. The Salsa20 algorithm was chosen because it takes up less memory compared to other algorithms. The secured data are the documents and the keywords. The contents of the document and keywords are encrypted into a new form, ciphertext. The ciphertext security level of this research is proven by active attack testing. But before that, the ciphertext is validated first with a test vector. Vector testing is done by matching the input and ciphertext in the journal. Vector testing results produce a valid status for each scenario. With the validation of the ciphertext in this study, data security is further tested using active attack method, the Known Plaintext Attack (KPA). The KPA attack on ciphertext was declared a failure in getting the key. Based on testing the time of encryption and decryption, it can be concluded that the difference in time of encryption and decryption is not large.